Citizenship and the Social Geography of Deep Neo-Liberalization - Gledhill, John (Anthropologica, 2022)
From the vantage point of the bleak social landscapes of the "divided cities" of Latin America, the meaningfulness of the focus on deepening the rights of citizenship that accompanied the shift to more democratic political regimes is far from obvious, despite some apparently positive developments accompanying the transition to neoliberalism. This paper examines the reasons for the resilience of neo-liberalism despite the popular protests that neo-liberal economic policies have provoked in many countries, arguing that the logic of neo-liberal rule systems has now permeated even the most "socially progressive" political parties and feeds off the diffuse effects of social transformation.